2015
DOI: 10.3390/ijms161226132
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Current Status of Evaluation System of Bioavailability and Related Pharmaceutical Technologies for Traditional Chinese Medicines—Flos Lonicerae Japonicae—Fructus Forsythiae Herb Couples as an Example

Abstract: Traditional Chinese medicines (TCMs) have attracted extensive interest throughout the world due to their long history of health protection and disease control, and the internalization of TCM preparations or patented drugs has been considered a wind vane in the process of TCM modernization. However, multi-target effects, caused by multiple components in TCMs, hinder not only the construction of the quality evaluation system (bioavailability), but also the application of pharmaceutical technologies, which result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 181 publications
0
6
0
1
Order By: Relevance
“…Because a high-degree chemical similarity does not equal a bioequivalence. Therefore, the establishment of a complete system for the determination of bioavailability using biological techniques is the key factor in the assessment of consistency of quality and the modernization of natural herbal medicines [117,118].…”
Section: Biological Consistency Evaluation Methodsmentioning
confidence: 99%
“…Because a high-degree chemical similarity does not equal a bioequivalence. Therefore, the establishment of a complete system for the determination of bioavailability using biological techniques is the key factor in the assessment of consistency of quality and the modernization of natural herbal medicines [117,118].…”
Section: Biological Consistency Evaluation Methodsmentioning
confidence: 99%
“…122 The quantity of NOc fabrication at 3 to 25 mM was continuously calculated, and the IC 50 values were found to be 12.4 and 10.1 mM for aand , and human neuroblastoma cells (SH-SY5Y). 131,132 The modied xanthones were found to exhibit the most potent antitumor activities by inducing apoptosis in HepG2 cell lines in a dose-dependent manner. 133 It was found that the efficiency of cell growth inhibition increased dramatically when the concentration of modied xanthones was increased.…”
Section: Xanthones and Xanthene-based Scaffoldsmentioning
confidence: 99%
“…133 It was found that the efficiency of cell growth inhibition increased dramatically when the concentration of modied xanthones was increased. 131,132 Jang et al reported that modied xanthones (Fig. 26) were selective agonist for TrkA receptor, showing a strong neurotrophic activity by selectively binding to TrkA, inducing its tyrosine phosphorylation, provoking outgrowth in PC12 cells, eliciting PI3-kinase/Akt and MAPK activation, thus preventing neuronal cell death.…”
Section: Xanthones and Xanthene-based Scaffoldsmentioning
confidence: 99%
“…Overall, PADP has positive effect on inhibiting the growth of cancer cells in patients with liver cancer, alleviating clinical symptoms of patients, improving their living quality, and increasing the survival period of patients. Due to the complex composition of traditional Chinese medicines ( 8 ), it is difficult for traditional pharmacological research methods to systematically explain the mechanism of action and signaling pathways of PADP on the treatment of liver cancer. Therefore, the mechanism of PADP on the treatment of liver cancer has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%